2021
DOI: 10.24193/jebp.2021.1.5
|View full text |Cite
|
Sign up to set email alerts
|

"Anxiety, Depression and Insomnia Conditions in Italian Nurses during the First and the Second Waves of the Covid-19 Pandemic"

Abstract: "Background: To assess the levels of anxiety, depression and insomnia among Italian nurses directly involved in the care of patients with Covid-19, considering the first and the second wave of the pandemic. Methods: An online questionnaire was administered on some pages of the nursing social networks and addressed precisely to nurses directly involved in the care of patients affected by Covid-19 in two different periods of the pandemic: during the first wave (March2020 - May 2020) and during the second wave (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Some studies had focused on a single second wave of infection [ 17 , 18 ]. A study comparing two waves of infection in India reported that HCW were less affected by psychological impacts during the second wave [ 19 ], but two Italian studies comparing psychological stress in the first and second waves reported no significant differences between the two waves [ 20 , 21 ]. These findings leave questions such as, if in different countries, with a variety in backgrounds or influencing factors, how can the negative psychological effects and severity in HCW during different waves of the pandemic differ?…”
Section: Introductionmentioning
confidence: 99%
“…Some studies had focused on a single second wave of infection [ 17 , 18 ]. A study comparing two waves of infection in India reported that HCW were less affected by psychological impacts during the second wave [ 19 ], but two Italian studies comparing psychological stress in the first and second waves reported no significant differences between the two waves [ 20 , 21 ]. These findings leave questions such as, if in different countries, with a variety in backgrounds or influencing factors, how can the negative psychological effects and severity in HCW during different waves of the pandemic differ?…”
Section: Introductionmentioning
confidence: 99%
“…Nurses might develop coping strategies to complete their heavy workloads and important professional changes, such as improving technical competencies in a very short time. Additionally, lack of PPE availability, perceptions of unsafe work environments, being isolated from family members to avoid contagion, and fear of the unknown new SARS-CoV-2 infection negatively influenced nurses' mental conditions during the pandemic [19][20][21][22][23][24]43]. In line with previous studies [44][45][46], a considerable portion of the healthcare workers participating in this survey were provisionally diagnosed with PTSD.…”
Section: Discussionmentioning
confidence: 56%
“…In this regard, of several studies in the literature showing PTSD among nurses [39] during the COVID-19 pandemic [19][20][21][22][23][24], few investigated PTSD in nursing students and very few compared nurses and nursing students during the COVID-19 pandemic. The present pilot study aimed to investigate PTSD symptoms in nurses according to sex and nursing experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations